Integrasi Quantum Teaching dan Lapbook: Pengaruhnya Terhadap Kreativitas Siswa SMA (Indo-MathEdu Intellectuals Journal, 2025)
This study aimed to investigate the effect of the quantum teaching model assisted by a lapbook on the creativity of tenth-grade students at SMA Negeri 1 Alu, Polewali Mandar Regency, West Sulawesi. This research adopted a quantitative approach with a quasi-experimental design, involving 42 students divided into an experimental group (quantum teaching with a lapbook) and a control group (conventional teaching). The cluster random sampling technique was used to determine the classes that were selected as research samples. The research instrument consisted of a creativity test with 15 items. Data analysis was performed using the independent sample t-test statistical method. The results revealed a significant difference in student creativity between the experimental group (mean posttest score of 73.14) and the control group (mean posttest score of 62.38), with p = 0.000 (p < 0.05). These findings indicated that the integration of quantum teaching and a lapbook effectively enhanced students’ creativity, as measured by indicators of curiosity, fluency, flexibility, originality, elaboration, and divergent thinking. This study concluded that quantum teaching combined with a lapbook can be an effective solution to foster students' creativity in biology teaching, particularly on the topic of ecosystems.